Mobility among secondary school leavers from selected district towns, Peninsular Malaysia - Sidhu, Manjit S. (Universiti Kebangsaan Malaysia, 1976)
This paper studies the mobility of school-leavers from six different towns which are district headquarters. It seeks to find out: (i) why school-leavers migrate (ii) to which areas do they migrate to and why? (iii); do destinations differ among the different school-leavers?